TransPoly: A theoretical model to quantify the dynamics of water transfer through nanostructured polymer films. (16th March 2020) - Almeida, Giana; Domenek, Sandra; Perré, Patrick
Abstract: Mass transfer of penetrants is among the most important physical properties of polymer films to properly ensure function during service. In the case of interaction between penetrants and polymer, non-Fickian diffusion can be observed. This phenomenon is described by numerous reports and a few models have been proposed. Nevertheless, few of them quantify Fickian and non-Fickian behaviour using parameters with clear physical meaning. The present work develops a new non-Fickian mass transport model: TransPoly (Transfer through Polymers). Based on coupled heat and mass transfer, it accounts for simultaneous Fickian transport and molecular relaxation. This model is applied to data of water vapour mass transfer in nanocomposites of polylactide and cellulose nanocrystals. The contribution of the non-Fickian mass transfer on water vapour sorption is highlighted. TransPoly can be applied to several kinds of polymers and used for prediction purposes once the parameters are determined on a learning database. Graphical abstract: Highlights: New model to study mass transfer through polymers ( TransPoly ) is proposed. Main parameters related to the diffusion process are quantified for PLA/CNC films. Fickian diffusion coefficient, molecular relaxation rate and time constant are quantified. Model is able to predict the mass transfer through films for different conditions. Nanoparticles contribute substantially to the relaxation controlled mass transport.